Auf die Lernbegleitung kommt es an! Konzepte und Befunde zu Praxisphasen in der Lehrerbildung - Hesse, Florian; Lütgert, Will (Verlag Julius Klinkhardt, 2020)
Within and outside Germany, practical phases in teacher education have been expanded in recent years. In contrast, empirical studies show that it is not primarily the duration of the internships but their qualitative design that is significant for the acquisition of competencies by the students. Against this background, the academic examination of concepts of learning support is gaining in importance. The authors in this volume take up this assumption and present ten context-bound learning support concepts and their empirical examination. Using qualitative and quantitative research methods, theory-based hypotheses are tested and framework conditions are included in the discussion. In this respect, the results of the studies presented promise on the one hand in-depth insights into the opportunities and challenges of learning support services in the school internship, and on the other hand they point to desiderata for further studies in this field of research.